2016
DOI: 10.1089/ars.2015.6494
|View full text |Cite
|
Sign up to set email alerts
|

18α-Glycyrrhetinic Acid Proteasome Activator Decelerates Aging and Alzheimer's Disease Progression inCaenorhabditiselegansand Neuronal Cultures

Abstract: Aims: Proteasomes are constituents of the cellular proteolytic networks that maintain protein homeostasis through regulated proteolysis of normal and abnormal (in any way) proteins. Genetically mediated proteasome activation in multicellular organisms has been shown to promote longevity and to exert protein antiaggregation activity. In this study, we investigate whether compound-mediated proteasome activation is feasible in a multicellular organism and we dissect the effects of such approach in aging and Alzhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 60 publications
6
51
0
Order By: Relevance
“…Model system Impact on Nrf2 and/or effect on thyroid function/morphology 1,5-Dicaffeoylquinic acid primary culture rat cortical astrocytes [188] mediates glutathione synthesis via Nrf2 A , NP [188] 18α-Glycyrrhetinic Acid HFL-1 human primary fibroblasts [189]; human neuroblastoma SH-SY5Y cells [190]; murine cortical neurons [190]; C. elegans [190] ↑Nrf2, ↑ proteasome subunits [189]; ↑Nrf2, ↑ oxidative stress resistance [190]; ↑ cellular lifespan [190]; ↑ organismal lifespan [190] 3-Caffeoyl, 4-dihydrocaffeoyl quinic acid Hepa1c1c7 cells [191] scavenges ROS, regulates HO-1 via PI3K/Akt-Nrf2 PtW, HP [191] Andalusol Conchitriol Lagascatriol PC12 cells [192] Nrf2 PtW A , NP, AO [192] Antroquinonol B-cell-deficient M [193] Nrf2 PtW A , T cells and NLRP3 I , NephP [193] Carnosic acid PC12 COS7 cells [194] Keap1/Nrf2 Ptw A via cysteine S-alkylation, NP [194] Carnosol PC12 cells [195] ↑Nrf2, ↑HO-1 expression via PI3K/Akt Ptw A , NP [195] Celastrol HaCaT cells [196]; 8505C and SW1736 cells [197] ↑HO-1 expression via ROS/Nrf2/ARE signaling [196]; ↓cell viability, ↑cytotoxic activity, AC [197] Emodin, Aloe emodin mouse primary microglia [198]; thyroid cancer cell line K1 [199] HO-1 and NQO1 induction via AMPK/Nrf2 signaling, AI, NP [198]; promotes apoptosis of K1 cells [199] Kahweol SH-SY5Y cells [199] HO-1 regulation via the PI3K and p38/Nrf2 PtW, NP [199] Kaurenoic acid RAW264.7 and HEK293 cells [200] Nrf2 A , AI [200] Linearol Sidol PC12 cells [201] ↓ROS production via Nrf2 antioxidant system modulation, NP, AO [201] Maslinic Acid…”
Section: Compoundmentioning
confidence: 99%
“…Model system Impact on Nrf2 and/or effect on thyroid function/morphology 1,5-Dicaffeoylquinic acid primary culture rat cortical astrocytes [188] mediates glutathione synthesis via Nrf2 A , NP [188] 18α-Glycyrrhetinic Acid HFL-1 human primary fibroblasts [189]; human neuroblastoma SH-SY5Y cells [190]; murine cortical neurons [190]; C. elegans [190] ↑Nrf2, ↑ proteasome subunits [189]; ↑Nrf2, ↑ oxidative stress resistance [190]; ↑ cellular lifespan [190]; ↑ organismal lifespan [190] 3-Caffeoyl, 4-dihydrocaffeoyl quinic acid Hepa1c1c7 cells [191] scavenges ROS, regulates HO-1 via PI3K/Akt-Nrf2 PtW, HP [191] Andalusol Conchitriol Lagascatriol PC12 cells [192] Nrf2 PtW A , NP, AO [192] Antroquinonol B-cell-deficient M [193] Nrf2 PtW A , T cells and NLRP3 I , NephP [193] Carnosic acid PC12 COS7 cells [194] Keap1/Nrf2 Ptw A via cysteine S-alkylation, NP [194] Carnosol PC12 cells [195] ↑Nrf2, ↑HO-1 expression via PI3K/Akt Ptw A , NP [195] Celastrol HaCaT cells [196]; 8505C and SW1736 cells [197] ↑HO-1 expression via ROS/Nrf2/ARE signaling [196]; ↓cell viability, ↑cytotoxic activity, AC [197] Emodin, Aloe emodin mouse primary microglia [198]; thyroid cancer cell line K1 [199] HO-1 and NQO1 induction via AMPK/Nrf2 signaling, AI, NP [198]; promotes apoptosis of K1 cells [199] Kahweol SH-SY5Y cells [199] HO-1 regulation via the PI3K and p38/Nrf2 PtW, NP [199] Kaurenoic acid RAW264.7 and HEK293 cells [200] Nrf2 A , AI [200] Linearol Sidol PC12 cells [201] ↓ROS production via Nrf2 antioxidant system modulation, NP, AO [201] Maslinic Acid…”
Section: Compoundmentioning
confidence: 99%
“…Treatment with 18α-glycyrrhetinic acid (18α GA) promotes the proteasome assembly and activity in HFL-1 human primary cells in an Nrf2-dependent manner leading to parallel decreased ROS levels [38]. The positive effects of 18αGA on proteasome status have been shown to be evolutionary conserved; verified at the level of a multi-cellular organism ( C. elegans ) [42]. The flavonoid quercetin, a known Nrf2 activator [88], was shown to enhance proteasome activities, to promote increased oxidative stress resistance and to confer enhanced longevity in HFL-1 cells [86].…”
Section: Conditions and Processes Where Redox Alterations Signal Chanmentioning
confidence: 99%
“…This study suggests that pharmacological activation of NRF2 is possible even in late life [86]. Moreover, a later study showed that this compound mediated SKN-1 and proteasome activation in C.elegans with beneficial effects on AD progression in relevant nematode models [134].…”
Section: Promising Therapeutic Potential For Nrf2 In Proteinopathiesmentioning
confidence: 59%